2013
DOI: 10.1371/journal.pone.0063092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Hematological Profile of Elite Road Cyclists during the 2010 and 2012 GiroBio Ten-Day Stage Races and Relationships with Final Ranking

Abstract: Cycling stage races are strenuous endurance events during which exercise-induced variations in hematological parameters are consistently observed. However, specific literature on such changes is scarce and published data have been derived from small samples of athletes. The aims of this study were: (1) to determine the hematological response to middle-term strenuous endurance; and (2) to determine whether a relationship exists between the athlete-specific hematological profile and final placement in a cycling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
(31 reference statements)
2
20
1
Order By: Relevance
“…Three blood collections were performed on the Chinese riders: 1 day before the start of the race (D-1) and on the rest day (D9) and the morning after the race had finished (D15). All blood sampling, handling, and transport, both in Australia and China, were performed in strict accordance with World Anti-Doping Agency (WADA) and UCI rules (44) to ensure consistency and reliability (30). Specifically, all blood tests were performed at rest between 0600 and 0900 without prior exercise and with cyclists seated for at least 10 min before collection with their feet on the floor (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three blood collections were performed on the Chinese riders: 1 day before the start of the race (D-1) and on the rest day (D9) and the morning after the race had finished (D15). All blood sampling, handling, and transport, both in Australia and China, were performed in strict accordance with World Anti-Doping Agency (WADA) and UCI rules (44) to ensure consistency and reliability (30). Specifically, all blood tests were performed at rest between 0600 and 0900 without prior exercise and with cyclists seated for at least 10 min before collection with their feet on the floor (1).…”
Section: Methodsmentioning
confidence: 99%
“…To date, there are a number of published studies that document changes in hematological variables such as hemoglobin concentration ([Hb]), hematocrit (Hct), percentage of reticulocytes (%Retics), and more recently, hemoglobin mass (Hbmass) during cycling stage races of 1-3 wk. In the largest cohort currently investigated, Lombardi et al (30) report decreased [Hb] and Hct values during the first half of a 10-day cycling race. Similar findings have been reported by others, albeit in much smaller cohorts (15,31,40).…”
mentioning
confidence: 99%
“…It is unknown how fast plasma volume returns to baseline after the end of an increased training load or multiday competition in high-level athletes, which is well known to be associated with a ~15-20% plasma volume expansion [1][2][3][4] and ~10% [Hb] reduction 1,2,[4][5][6][7][8] in both moderate and highly trained subjects. The time course of plasma volume reduction and its effect on primary anti-doping-related hematological variables such as [Hb] is of high importance for anti-doping purposes and in particular for interpretation of blood profiles in the Athlete Biological Passport (ABP).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a better understanding of hematological responses associated with different sporting disciplines is necessary. Hemodilution, especially due to prolonged exercise, has been well‐described as a confounding factor to the hematological passport . However, ABP results of this phenomenon have not yet been fully described in the context of Ironman triathlons, nor have the extent and duration post‐exercise been established.…”
Section: Discussionmentioning
confidence: 99%
“…8,19 Notably, anecdotal evidence has shown that dramatic decreases in hemoglobin occur during routine biological passport monitoring of long-distance triathletes in the days following competitions. These suspected hemodilution effects in turn affect the values present in the biological passport, 10,16,17 potentially resulting in the presentation of atypical profiles, and must be considered by ABP experts. Thus, the aim of this study was to assess the hematological changes and their relation to the ABP for up to one week following completion of an Ironman triathlon.…”
Section: Introductionmentioning
confidence: 99%